THE PECULIARITIES OF BREEDING NEW CULTIVARS OF HEMP FOR SOWING AT “THE INSTITUTE OF ORGANIC FARMING”, LLC - Pylypchenko, A. V.; Piskovyі, М. B. (Scientific Progress & Innovations, 2020)
Today the group of “Arnika”companies located in Hlobyne, Poltava region is one of the largest enter- prises of Ukraine and the world cultivating crops using organic farming technologies. It is clear that during the transition from traditional technology to organic production a number of problems arose. In order to solve them, it was necessary to apply the existing experience as well as new scientific researches. Hemp pro- duction is one of the branches of Ukraine’s agriculture, which mainly meets the requirements of organic farming. In this matter, the essential role is played by the biological properties of the crop and the demand for hemp products. The biological peculiarity of hemp is that it almost does not need chemical protection from pests and diseases and therefore the application of pesticides. Hemp is a crop, which under the condi- tion of following the cultivation technology fights weeds itself. In Ukraine, hemp production has always been one of the priority branches of agriculture. It takes a prominent place not only in Europe but in the whole world as well. The scope of applying raw materials from hemp is significantly increasing. Besides the tradi- tional use in light, construction, pulp-paper, automobile, aircraft construction, and chemical industries, hemp products began to be used in manufacturing medicines, perfumes, cosmetics, high-quality oils, supple- ments to various food products, etc. Particularly the latter cases of using hemp require the application of ecologically friendly products, which would have more demand, higher evaluation, and cost at the market. The creation of the plant cultivars and hybrids, which contribute to the increase of productivity and adapta- bility of artificial ecosystems, is on the list of the most relevant agro-technical measures of technologies’ bi- ologization. The scientific research, conducted during 2014−2018 was devoted to this issue, and it is still being continued. In this article, we have tried to show our researches, achievements, and conclusions with the aim to breed new hemp cultivars for sowing appropriate for traditional cultivation technologies and what is most important adapted to organic farming technologies.